PERSEPSI PEMBUDIDAYA IKAN KOLAM TERHADAP PROGRAM MINAPOLITAN DI DESA BASARANG KECAMATAN BASARANG KABUPATEN KAPUAS - Tulus Bujur; Idiannor Mahyudin; M. Adriani; Dini Sofarini (Universitas Lambung Mangkurat, 2015)
The research was conducted in the village Basarang covering RT.1, RT.2, RT.4 and RT.5 Basarang district of central borneo province. Analyze perception of fish against minapolitan development and the factors that influence the development minapolitan such as education, employment, income, length of residence, and extension especially fishery. This study uses a survey approach in which the data sample drawn from the population. In addition, observation, interviews and questionnaires. Public perception of fish farmers in the village Basarang district Kapuas and surrounding counties Basarang be position minapolitan program, meaning that the fish farmers fully support the development of the area in the hope of later minapolitan program beneficial to improve the local economy fish farmers in particular and society in general. From the results of research in the field, that the factors that influence people’s perception of the fish farmers minapolitan program is education, employment, income, length of residence and education. As a reference for stakeholders to engage community fish farmers in decision-making in the context of policy and the welfare of society in the development of the area in the village Basarang minapolitan program and provide policy recommendations for the govemment related activities minapolitan future development.